2012
DOI: 10.1002/mc.21981
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of JWA promotes tumor invasion and predicts poor prognosis in human hepatocellular carcinoma

Abstract: We previously identified JWA as a novel microtubule-associated protein (MAP), which is implicated in carcinogenesis and tumor progression. The aims of the present study were to investigate the biological action and the prognostic significance of JWA in hepatocellular carcinoma (HCC). Quantitative real-time PCR and Western blot were used to detect JWA mRNA and protein expression, respectively, in stepwise metastatic HCC cell lines and HCC tissues. Short hairpin RNA was used to inhibit JWA expression in HCC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
3
21
0
1
Order By: Relevance
“…Numerous studies indicate that deregulated signaling of Rho GTPases plays an important role in HCC progression and metastasis (9). RhoA pathway associates with venous invasion, cell differentiation and poor prognosis (22), correlating with tumor progression and metastasis (23)(24)(25). Rac1 GTPase is crucial for actin cytoskeleton reorganization at the cell cortex and is involved in processes of HCC migration and invasion (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that deregulated signaling of Rho GTPases plays an important role in HCC progression and metastasis (9). RhoA pathway associates with venous invasion, cell differentiation and poor prognosis (22), correlating with tumor progression and metastasis (23)(24)(25). Rac1 GTPase is crucial for actin cytoskeleton reorganization at the cell cortex and is involved in processes of HCC migration and invasion (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, JWA protein expression levels are closely correlated with the occurrence, invasion and metastasis of malignant tumors (15). Using liver cells with different metastatic potential, a previous study revealed that reduced expression levels of JWA protein resulted in increased metastasis potential (6). Previous results have indicated that downregulation of JWA expression may affect cell function, such as proliferation, apoptosis, migration and invasion via the mitogen-activated protein kinase/extracellular signal-regulated kinase pathway of mitogen-activated protein kinase signaling cascades (16).…”
Section: Discussionmentioning
confidence: 99%
“…MEF cells (1x10 6 ) were seeded in a 100 mm culture dish. NU1025 (Sigma-Aldrich; Merck KGaA Darmstadt, Germany), a specific inhibitor of PARP-1, was used to inhibit the function of PARP-1 in MEF cells.…”
Section: Expression Of Emt-related Proteins and Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Para este ensaio foi utilizado o Matrigel, uma membrana basal reconstituída, que pode propiciar condições similares ao observado em microambiente tumoral, uma vez que é proveniente do sarcoma de murinos. Em adição, esta matriz permite rápida formação das estruturas tubulares em sistema 3D, as quais são facilmente quantificáveis (ARNAOUTOVA et al, 2009;BAZZA et al, 2010 , 1996), principal ligante das células tumorais mamárias a estes componentes, bem como a expressão de α 3 β 1 , principal integrina ligante de laminina (CHEN et al, 2014), poderiam contribuir para a compreensão da seletividade da ação inibitória do pS100A9m sobre a célula tumoral.…”
Section: Efeito Do Ps100a9m Na Migração De Células Tumorais Llc Wrc25unclassified